24(-2x+1)=-7(5x+2)-3x

Simple and best practice solution for 24(-2x+1)=-7(5x+2)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24(-2x+1)=-7(5x+2)-3x equation:


Simplifying
24(-2x + 1) = -7(5x + 2) + -3x

Reorder the terms:
24(1 + -2x) = -7(5x + 2) + -3x
(1 * 24 + -2x * 24) = -7(5x + 2) + -3x
(24 + -48x) = -7(5x + 2) + -3x

Reorder the terms:
24 + -48x = -7(2 + 5x) + -3x
24 + -48x = (2 * -7 + 5x * -7) + -3x
24 + -48x = (-14 + -35x) + -3x

Combine like terms: -35x + -3x = -38x
24 + -48x = -14 + -38x

Solving
24 + -48x = -14 + -38x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '38x' to each side of the equation.
24 + -48x + 38x = -14 + -38x + 38x

Combine like terms: -48x + 38x = -10x
24 + -10x = -14 + -38x + 38x

Combine like terms: -38x + 38x = 0
24 + -10x = -14 + 0
24 + -10x = -14

Add '-24' to each side of the equation.
24 + -24 + -10x = -14 + -24

Combine like terms: 24 + -24 = 0
0 + -10x = -14 + -24
-10x = -14 + -24

Combine like terms: -14 + -24 = -38
-10x = -38

Divide each side by '-10'.
x = 3.8

Simplifying
x = 3.8

See similar equations:

| x-29=87 | | 29+x=87 | | y=5x^2+7 | | 6+87b=9 | | 6+87b= | | 1/7^2-3/7x=0 | | y=sinx(ln(5x)) | | f(x)=5x^2+7 | | 22/2=m/3 | | (5x^2y)*(7x^2-4xy^2+2y^3)= | | 2x+1+-3x+5=3(x+8) | | 2x+1+-3+5=3(x+8) | | 3xsquared+23x-500=0 | | 9x-3+5x=2x+5-4x | | 9x+6=8x+3 | | 3x+6=10-5x | | 2x+5-3X-1+4X=49 | | a/2-3=7 | | 4x^2-9y^2+z=0 | | 10x^2-11x-80=0 | | R=0.15966(499) | | 3=x-3-5x | | .15966(499)= | | 4y-1=x | | Y=x^3-5x^2+2x-10 | | 48(x^2)-78(x)+33=0 | | 4cos^2x+3cosx=1 | | x-128=2/5x | | y=25+sin(2*pi*x) | | 5x-2y=98 | | 20x^2-60x=0 | | (3y^2+3xy+x^2)dx=(x^2+2xy)dy |

Equations solver categories